Some considerations in investigating synchronous online delivery of English courses: interfacing qualitative and quantitative paradigms - Pramela Krish (Penerbit UKM, 2008)
E-learning is not just another add-on to the existing system of learning. It is a technology that is transforming our educational institutions and how we conceptualise and experience teaching and learning. Teaching online is becoming more flexible and innovative in its preparation and delivery, as content and activities can be placed on websites for students both as supplement to lectures or as replacement for them. This paper discusses how a doctoral dissertation was designed to gather information on three areas related to the synchronous online delivery of English courses namely teaching and learning, technology, and management in a virtual institution of higher learning. It explains the design of the study and its rationale within the qualitative and quantitative paradigms. The discussion in this paper also attempts to highlight plausible issues that researchers may encounter when conducting research in a technology enhanced context and suggests practical way to consider.